The attitude of Malaysian Indian plantation community as portrayed in selected Malaysian Tamil novels - Govindasamy Kolendai (2021)
The objective of this research is to identify the socioeconomic status of Malaysian Indian plantation community, to analyze their attitude and to study the correlation between these two variables as portrayed in Malaysian Tamil novels. The qualitative research method was used and data collection was carried out using description and analysis. The Theory of Reasoned Action was used to analyze the attitude and behavior according to four elements which are intention, belief, reflection and behavior. Six Malaysian Tamil novels with the background of Malaysian Indian plantation community were used for this study. Twentynine characters from the selected novels were used to identify their socio-economic status; to analyze their attitude and to study the correlation between these two variables. The findings show that there are twelve characters portray high socioeconomic status with positive attitude while the other seventeen portray low socioeconomic with negative attitude. The findings also reveal that there is a correlation between their socioeconomic status and their attitude. The conclusion of this research is, the socioeconomic status of the Malaysian Indian plantation community is determined by their attitude. The research implies that the Malaysian Indian plantation community has to change their attitude into positive in order to enjoy high socioeconomic status like others.